Formigas como bioindicadoras da trajetória sucessional de restauração de uma floresta ripária - Silva, Sabrina Gabriele da (Universidade Federal de São Carlos, 2025)
Anthropogenic activities can negatively affect ecosystems such as riparian environments, leading to biodiversity loss and consequently impairing the functioning of ecosystem processes and services. In this context, ecological restoration is essential to recover both biodiversity and ecosystem functioning. The use of bioindicators is an important tool for monitoring the progress of forest regeneration, and ant communities, in particular, stand out due to their high sensitivity to environmental changes. In this study, we evaluated whether soil ant communities, ten years after the restoration of a degraded riparian area (restored site), had recovered in comparison with adjacent forest remnants (forest) and pasture areas. Ants were sampled using pitfall traps in six plots per vegetation type, and individuals were identified to the morphospecies level. Our results indicate that the restored site and the forest remnant harbored ant communities with similar diversity values, both being more diverse than the pasture, which exhibited higher species dominance. In addition, species composition was also similar between the restored site and the forest, whereas the pasture showed a distinct composition, possibly due to lower species richness and higher dominance. Therefore, riparian forest restoration allows the recovery of ant diversity after ten years, potentially contributing to the reestablishment of ecosystem processes mediated by this important group of soil fauna.
Ants as bioindicators of the successional trajectory of riparian forest restoration
Keywords: biodiversidade; bioindicadores; comunidade de formigas; restauração; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA APLICADA; 15. Vida Terrestre